The Influence of Company Characteristics on Audit Report Lag: Auditor Characteristics as a Moderating Variable - Putri, Nurul Alifah; Dyah Febriantina Istiqomah (Accounting and Finance Studies, 2024)
Research Aims: This research examines the influence of profitability, liquidity, solvency, audit committee size, board of directors’ size, and company size on audit report lag, with auditor reputation as a moderating variable. Design/methodology/approach: The research sample consisted of 61 energy sector companies listed on the Indonesia Stock Exchange during the 2020-2022 period, so the total research observation subjects were 183 data. Data analysis in this research uses panel data regression analysis. This research uses advanced statistical and econometric data analysis software, namely Eviews Enterprise 12 Software. Research Findings: The research results show that profitability has a negative effect on audit report lag. Meanwhile, liquidity, solvency, the size of the board of directors, and company size positively affect audit report lag. The size of the audit committee does not affect audit repro lag. Auditor reputation moderates the influence of profitability, liquidity, the size of the board of directors, and company size on audit report lag. Theoretical Contribution/Originality: This research is expected to enrich the literature regarding factors that influence audit report lag and provide a solid basis for companies to optimize the timing of publishing financial reports by considering these factors in energy sector companies.